Antimicrobial susceptibility profile of Vibrio cholerae strains isolated at a tertiary care medical centre in New Delhi, India - Uppal, Beena; Mehra, Bhanu; Panda, Pragyan Swagatika; Kumar, Shyam Kishor (International Journal Of Community Medicine And Public Health, 2017)
Background: Vibrio cholerae is a common cause of acute diarrhea in India. Extensive and injudicious use of antimicrobials has led to the emergence of V. cholerae strains that are resistant to several antibiotics. The present study was conducted to document the antibiogram of V. cholerae strains isolated at an urban health centre in New Delhi. The present study was a retrospective, record-based analysis conducted from January to December 2015, at the Department of Microbiology of a tertiary care teaching institute. Methods: Stool samples received in the laboratory were processed as per standard microbiological techniques and all the V. cholerae strains isolated were subjected to antimicrobial susceptibility testing as described in the Clinical and Laboratory Standards Institute (CLSI) guidelines. Data was analyzed using the Epi info software, version 3.5.3, and results depicted in the form of descriptive statistics. Results: Vibrio cholerae was isolated in 70 of the 2340 stool samples processed during the study period. Serogrouping revealed that 66 (94.3%) of the isolates were V. cholerae O1 serotype Ogawa, while non-O1 non-O139 serogroups constituted 4 (5.7%) isolates. The strains exhibited resistance to nalidixic acid (94.3%), ampicillin (92.9 %), ciprofloxacin (55.7%), cefotaxime (41.4%), gentamicin (22.9 %) and amikacin (7.1 %). Conclusions: Our study highlights the significance of regular surveillance of antimicrobial resistance profile of V. cholerae strains for proper management of cholera.